Análisis Internacional - PE64 - 202101 - Dominguez Navarrete, Cristhiam Roberto (2021)
Description: This course searches to strength the capacity of students to confront a double challenge that our age of overwhelming news coverage provokes: First, how can they select which conflicts are more important than others and secondly, how can they acquire basic knowledge that will enable them to understand these complex events happening in diverse parts of the world, and later explain them in an easy and contextualized way to people of different cultural levels. The course also provides students with tools of interpretation and critical thinking of a complex world in which only exits a constant characteristic: change. Many centrifugal forces push societies towards nationalism, xenophobia, racism and isolation but globalization is an irreversible fact that will also force people to move according to centripetal forces of commercial and geopolitical treaties, partnership of governments, regional and global institutions in order to solve conflicts and problems such as climate change, terrorism, wars and massacres, etc. Also, the world needs, urgently, changes in the liberal political system which characterizes the western societies in order to approach challenges such as artificial intelligence, new communicational and biological technologies, etc. The course seeks to aid students¿ understanding of the difficulties, dilemmas and responsibilities in learning contexts (geographical, historical, ethnic, religious, ideological, cultural, economic, etc.) to help them approach in depth and with professional honesty to any conflict. The students will be exposed as tools of learn to critical readings, journalist investigation, comparative methods of analysis, debates, and exploration of how technologies are used by people who undergo conflicts. Purpose: Theoretical Course of the Career of Communication and Journalism intended for students of the seventh cycle. It seeks to develop the general competencies of Critical thinking (level 3), Analysis and interpretation of reality 1(level 3) and journalist investigation (level 3). The course also seeks to prepare students to be skilled professionals capable to master information, opinions, analysis and projects of international current events as well as to produce journalistic works working places of the country and abroad. In order to achieve that the course will provide tools to develop, not only knowledge and rational tools for the students, but also encouraging the develop of emotional intelligence in order to make them sensitive personas interested in human rights and conscious of not being indifferent to the suffering of others. In order to achieve this there will be many topics and messages focusing on the main factor of all factors of analyzing topics and conflicts: the human being.